2020
DOI: 10.1016/j.coelec.2020.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical pressure impedance spectroscopy for investigation of mass transfer in polymer electrolyte membrane fuel cells

Abstract: Mass transfer phenomena in membrane fuel cells are complex and diversified, because of the presence of complex transport pathways including porous media of very different pore sizes, and possible formation of liquid water. Electrochemical impedance spectroscopy, although allowing valuable information on ohmic, charge and mass transfer phenomena, may nevertheless appear insufficient below 1 Hz. Use of another variable i.e. back pressure as excitation variable for electrochemical pressure impedance spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…EIS method is a powerful tool to screen the conductive properties of the nanomaterials modified electrodes, and the changes are related with interfacial features and thus permits to realize the chemical alteration and progressions linked with the conductivity on the surface of electrode [68] . The EIS Nyquist plots obtained for all Ni foam modified electrodes were further used for evaluating electro‐oxidation of hydrazine under identical experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…EIS method is a powerful tool to screen the conductive properties of the nanomaterials modified electrodes, and the changes are related with interfacial features and thus permits to realize the chemical alteration and progressions linked with the conductivity on the surface of electrode [68] . The EIS Nyquist plots obtained for all Ni foam modified electrodes were further used for evaluating electro‐oxidation of hydrazine under identical experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These effects could include the response time of the sensor used to monitor the perturbation and output, as well as the additive effects of the fuel cell feed conditioning system which can also be affected by particular perturbations. This was shown by Shirsath et al [18], who identified that the contribution of the humidifier system affected their measurements in a certain frequency range.…”
Section: Critical Remarks and Conclusionmentioning
confidence: 79%
“…The application of EPIS on PEMFCs was performed by Engebretsen et al [12] and more recently by Shirsath et al [18]. Both groups only conducted experiments under galvanostatic conditions registering the voltage responses and determining the EPIS transfer function Z V/P (see Table 3).…”
Section: Frequency Response Methodologies Based On Nonelectrical Quantitiesmentioning
confidence: 99%
See 2 more Smart Citations